The Gendered Division of Labor in Brazilian Political Science Journals - Candido, Marcia.; Luiz Augusto Campos; Feres Júnior, João; Feres Júnior, João (Brazilian Political Science Review, 2021)
This article analyzes the gendered division of labor in Brazilian political science. We seek to answer two questions: what are the predominant topics in political science that are being published in the discipline’s journals? How are women and men’s authorship distributed in these journals? The methodology involved three stages. First, we built a corpus with 2,363 articles that were classified as ‘political science and international relations’ by the Coordination for the Improvement for Higher Education Personnel (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – CAPES) and published in the most prominent Brazilian journals between 2005 and 2018. Next, we scraped abstracts and other bibliographic information from publications in the Scientific Electronic Library Online (SciELO) platform and used a topic modeling technique to identify the most recurrent topics. Finally, we associated the identified topics with the authors’ gender. The data was examined based on two specific types of the gendered division of labor: the ‘horizontal’ and the ‘vertical’. Our results show that women and men as first authors tend to cluster around specific topics (horizontal division), but we did not find a tendency in journals to reject works on the topics in which women are better represented. In other words, differently from what was found by the international literature, the Brazilian journals in our sample do not seem to grant a lower status to these topics (vertical division). It is noteworthy, however, that men are the majority of first authors in all topics, including feminism.